Cousinia brevicaulis sp. nov. (sect. Lasiandra) for the flora of Iran. (16th March 2016) - Attar, Farideh; Mozaffarian, Valiollah; Mirtadzadini, Mansour
Abstract : Cousinia brevicaulis is described and illustrated as a new species from eastern Iran. This species belongs to the C . sect. Lasiandra Bunge as defined by hairy anther tube, yellow, pale yellow or rarely milky flowers, monocarpic growth form and corymbose branching of stem. It is easily distinguished from other species of the section by its very short‐stemmed habit. The new species is distributed in the same region as other species of C . sect. Lasiandra .